Hipnoterapi Dalam Manajemen Nyeri Pada Pasien Kanker: A Systematic Review - Sartika, Dwi; Kariasa , I Made; Amelia, Amelia; Maria , Riri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Cancer remains one of the leading causes of mortality worldwide, with over 20 million newly diagnosed cases and nearly 10 million deaths globally, as reported by the International Agency for Research on Cancer (IARC) in 2020. In Indonesia, the incidence reached 408,661 new cases with 242,988 cancer-related deaths recorded in 2022. This growing burden has resulted in numerous clinical implications, with pain identified as the most frequently reported symptom among cancer patients, significantly impairing their quality of life. Among emerging approaches in pain management, non-pharmacological interventions such as hypnotherapy have gained attention due to their potential to reduce pain intensity without inducing serious adverse effects. This systematic review aims to evaluate the effectiveness of hypnosis therapy in managing cancer-related pain by analyzing six selected studies sourced from five international databases: ScienceDirect, EBSCO, PubMed, ProQuest, and Sage Journals. All included studies met the eligibility criteria, comprising randomized controlled trials (RCTs) and one meta-analysis, published within the last ten years. Five out of the six studies demonstrated that hypnosis interventions were effective in reducing pain intensity, while one study showed no statistically significant effect. Additionally, several studies explored integrative approaches combining hypnosis with complementary modalities such as music therapy and cognitive behavioral therapy. The findings of this review suggest that hypnotherapy serves as a promising complementary intervention to support effective pain management in oncology care. Further research employing more rigorous methodologies and larger sample sizes is recommended to strengthen the evidence base regarding its clinical utility.